Design Variations of Internal Baffle Walls to Reduce the Sloshing Effect in a Downscaled Flexitank - Amir Saifuddin, Muhammad Danial; Yong, Tze Mi; Muhammad Rusydi,; Nor Izwan Shah,; Alycia Yap Ching Hui,; Ch’Ming Wei,; Nofrizalidris Darlis,; Norrizal Mustaffa,; Omar Abu Hassan,; Shaiful Rizal Masro,; Jumadi Abdul Sukor,; Khairul Nizam Mustafa,; et al. (Progress in Engineering Application and Technology, 2024)
This study aimed to reduce sloshing in flexitanks by investigating various internal baffle wall designs. Sloshing, the movement of liquid causing instability and potential damage, led researchers to explore internal baffle walls as a solution. Five designs—Slot, Circular, 90% Plate, Rectangular, and Cross-X—were tested following ASTM D999-2015 standards. The method involved measuring sloshing cessation time across three cycles in a transportation simulator. The data revealed the Cross-X design as highly effective, reducing sloshing to under seven seconds. Additionally, using a flexible bend sensor, the slot design showed effectiveness at speeds between 5 and 10 but faced challenges at speed 15, indicating limitations at higher speeds. In conclusion, this research thoroughly examined various internal baffle wall designs, identifying the Cross-X design as particularly efficient in swiftly reducing sloshing, highlighting its crucial role in enhancing the safety of liquid cargo transportation.